2000
DOI: 10.4049/jimmunol.165.1.271
|View full text |Cite
|
Sign up to set email alerts
|

An IFN-γ-Inducible Transcription Factor, IFN Consensus Sequence Binding Protein (ICSBP), Stimulates IL-12 p40 Expression in Macrophages

Abstract: IL-12 is a cytokine that links innate and adaptive immunity. Its subunit p40 is induced in macrophages following IFN-γ/LPS stimulation. Here we studied the role for IFN consensus sequence binding protein (ICSBP), an IFN-γ/LPS-inducible transcription factor of the IFN regulatory factor (IRF) family in IL-12 p40 transcription. Macrophage-like cells established from ICSBP−/− mice did not induce IL-12 p40 transcripts, nor stimulated IL-12 p40 promoter activity after IFN-γ/LPS stimulation, although induction of oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
177
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 173 publications
(188 citation statements)
references
References 55 publications
10
177
1
Order By: Relevance
“…The critical role of IFN mediation of tissue injury was supported by studies showing that when IFN-c was inhibited, IL-12 alone failed to elicit tissue injury in lupus nephritis [38][39][40]. Fantuzzi et al [41] showed decreased production of the pro-inflammatory molecules IFN-c and IL-18 in IRF-1 -/-mice when challenged with inflammatory stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…The critical role of IFN mediation of tissue injury was supported by studies showing that when IFN-c was inhibited, IL-12 alone failed to elicit tissue injury in lupus nephritis [38][39][40]. Fantuzzi et al [41] showed decreased production of the pro-inflammatory molecules IFN-c and IL-18 in IRF-1 -/-mice when challenged with inflammatory stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it was shown that IRF-8 is an essential factor for proper functioning of mature macrophages. For example, IRF-8 null mice fail to mount Th1-mediated immune response, since they fail to produce the IL-12 p40 subunit (Wang et al 2000). Similarly, IRF-1 -/-are also devoid of Th1 responses due to deficiency of the same IL-12 subunit (Taki et al 1997; Lohoff et al 1997).…”
Section: Interferon (Ifn) Regulatory Factor-8 (Irf-8) Also Known As mentioning
confidence: 99%
“…Unlike other IRF members, IRF-8 is capable of binding to its target DNA sequence only following association with either IRF-1 and IRF-2 or non-IRF transcription factors, such as PU.1, an essential factor for hematopoiesis (Sharf et al 1997;Wang et al 2000;Dahl and Simon 2003) The domain essential for these protein-protein associations, termed IRF Association Domain (IAD), is conserved among all other IRF members excluding IRF-1 and IRF-2. The association modules of IRF-1 and IRF-2 with IRF-8 were identified as PEST domains, enriched with proline, glutamic acid, serine, and threonine, originally shown in PU.1 .The specific partner that interacts with IRF-8 dictates not only the DNA binding site but also the transcriptional activity e.g.…”
Section: Interferon (Ifn) Regulatory Factor-8 (Irf-8) Also Known As mentioning
confidence: 99%
See 1 more Smart Citation
“…8 Phosphorylated STAT1 dissociates from the receptor, dimerises and translocates to the cell nucleus, where it regulates gene expression either directly (for example, CD54, CXCL10 and CCL2) [9][10][11] or indirectly via the induction of transcription factors such as IRFs and CIITA (for example, IL12B, B2M and major histocompatibility complex). 12,13 Although STAT1 is the main mediator of IFN-g responses, IFN-g has also been reported to induce STAT3 or STAT5 phosphorylation. 14 Besides the JAK2-binding site, the intracellular domain of IFN-gR2 contains a BAX-inhibiting domain 15 and an internalisation motif 16 (Figure 1).…”
Section: Introductionmentioning
confidence: 99%